The Chance to Believe - Button, Dick (Tufts Archival Research Center, 2006)
Dick Button, five-time World Champion, describes how, during a skating exhibition in Prague in 1948, he was showered with oranges wrapped in messages from the Czech people, messages which underscored his belief in the importance of political freedom. Audio also contains an Advertisement for This I Believe book, Volume II.